The art of ‘looking’ : a technical analysis of Alexis Preller’s Man in the Sun - Loubser, Maggi (University of Pretoria, 2022)
Mini Dissertation (MSocSci (Tangible Heritage Conservation))--University of Pretoria, 2021.